2015
DOI: 10.1016/j.cll.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia miyamotoi Disease

Abstract: Synopsis Borrelia miyamotoi disease (BMD) is a newly recognized borreliosis globally transmitted by ticks of the Ixodes persulcatus species complex. Once considered to be a tick symbiont with no public health implications, B. miyamotoi is increasingly being recognized as the agent of a nonspecific febrile illness often misdiagnosed as acute Lyme disease without rash, or as ehrlichiosis. The frequency of its diagnosis in the northeastern U.S. is similar to that of HGA. A diagnosis of BMD may be confirmed by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…For immunocompetent patients, symptoms were similar to those observed in the aforementioned studies (e.g., fever, headache, malaise) (86, 89, 90, 106, 107). One US patient did not seek treatment, providing additional evidence that B. miyamotoi can result in recurrent fever and be self-resolving, similar to other relapsing fever infections (92, 110).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…For immunocompetent patients, symptoms were similar to those observed in the aforementioned studies (e.g., fever, headache, malaise) (86, 89, 90, 106, 107). One US patient did not seek treatment, providing additional evidence that B. miyamotoi can result in recurrent fever and be self-resolving, similar to other relapsing fever infections (92, 110).…”
Section: Introductionsupporting
confidence: 80%
“…However, additional symptoms characteristic of relapsing fever have not been demonstrated, namely rapid symptom onset with a crisis event suggesting B. miyamotoi infection is not synonymous with relapsing fever and is rather a relapsing fever-like illness (90). This should not be surprising given the different lifestyle of B. miyamotoi compared to the vast majority of relapsing fever spirochetes.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies are needed to determine the probability of B. miyamotoi transmission occurring after partial or complete blood meals by single infected larval or adult female ticks. This is particularly important in the case of the larval stage since the peak seasonal distribution of human acute B. miyamotoi infections in the northeastern United States appears to extend into August, when I. scapularis larvae rather than nymphs are most active (Molloy et al, 2015; Telford et al, 2015). We also cannot rule out the possibility that nymphs infected as larvae through feeding on an infectious blood meal host may differ in their efficiency to transmit B. miyamotoi as compared with transovarially infected nymphs.…”
Section: Discussionmentioning
confidence: 99%
“…The low percentage of cases with a relapse of fever may be due to the frequent use of empiric antibiotic therapy early in the course of febrile illnesses in patients with tick exposures. Although evidence of antigenic variation, which drives the relapsing course of other relapsing fevers due to borrelia, has not been demonstrated clinically or in an animal system thus far for B. miyamotoi [7], it has been shown that this species does have the genetic apparatus for this variation [16]. The typical duration of the initial fever episode in the soft tick transmitted relapsing fevers (TBRF) is 3 days, while that of louse-borne relapsing fever (LBRF) is 5.5 days [17].…”
Section: Discussionmentioning
confidence: 99%
“…ticks that potentially transmit Borrelia burgdorferi sensu lato [13]. However, in total less than 100 patients with this hard-tick transmitted infection have been reported on in the United States and for fewer than 10 of these patients were any of the specific clinical and laboratory data presented [47]. Cases have also been reported from Russia, the Netherlands and Japan [810].…”
mentioning
confidence: 99%